Impact of a computerised clinical decision support system on vancomycin loading and the risk of nephrotoxicity. (May 2021) - Chun, June Young; Song, Kyoung-Ho; Lee, Dong-eun; Hwang, Joo-Hee; Jung, Hyun Gul; Heo, Eunjeong; Kim, Hyung-sook; Yoon, Seonghae; Park, Jeong Su; Choe, Pyoeng Gyun; Chung, Jae-Yong; Park, Wan Beom; et al.
Highlights: Appropriate loading dose of vancomycin is rarely prescribed in real world settings. We introduced a computerised clinical decision support system for vancomycin loading. Vancomycin CDSS increased the initial trough level, without increased risk of nephrotoxicity. Abstract: Background: A vancomycin loading dose is recommended for the treatment of serious methicillin-resistant Staphylococcus aureus (MRSA) infections. However, clinicians often do not adhere to these recommendations, mainly due to nephrotoxicity risk, unfamiliarity with the guideline, or complexity of calculating an individual dose. Therefore, we introduced a computerised clinical decision support system (CDSS) for vancomycin loading (hereafter Vancomycin CDSS) to promote the use of vancomycin loading dose. Methods: We describe a quasi-experimental study spanning 6 months before and 18 months after the deployment of a Vancomycin CDSS. The Vancomycin CDSS was integrated into the hospital's electronic medical record system in the form of a vancomycin order set. Our primary endpoint was the incidence of nephrotoxicity; the secondary endpoint was mean initial vancomycin trough levels. We also conducted a survey to evaluate the reasons why clinicians opted not to utilise a vancomycin loading dose. Results: After implementation of Vancomycin CDSS, 363 out of 746 patients (49 %) who were first administered vancomycin received a loading dose. We did not find significant differences in nephrotoxicity between the pre- and post-intervention groups, nor between the loading- and non-loading groups. In the pre-intervention group, the mean initial vancomycin trough level was 7.10 mg/L, which was significantly lower than that in the post-intervention group of 11.11 mg/L. In the vancomycin loading group, the mean initial trough level was 11.95 mg/L, compared to 7.55 mg/L in the non-loading group. The main reason stated for not prescribing a vancomycin loading dose was concern about nephrotoxicity. Conclusion: Introduction of the Vancomycin CDSS did not increase nephrotoxicity and increased the mean initial dose and trough level of vancomycin.